Mapping of Major Land Use Land Cover Dynamics and Its Driving Factors: A Case Study of Nepalgunj Sub-Metropolitan City, Banke, Nepal - Prajwol Babu Subedi; Prakash Ojha; Amit Adhikari; Suman Acharya; Seema Acharya (Indonesian Journal of Social and Environmental Issues (IJSEI), 2022)
Understanding changes in Land Use Land Cover (LULC) is essential for managing and monitoring natural resources and development, particularly where urbanization is expanding. So, this study aimed to assess the level of changes in LULC of Nepalgunj Sub-metropolitan city using temporal Landsat satellite imageries of 1996, 2008, and 2020 AD, and the key drivers of LULC change were observed through a purposive household survey (N=140) with a sampling intensity of 0.5%. LULC maps were generated using initial unsupervised and later supervised classification. LULC changes were computed using the post-change detection classification technique. LULC map of 1996 AD, 2008 AD, and 2020 AD showed accuracy of 84.44 %, 85.45%, and 83.64% with a kappa value of 0.8381, 0.8497, and 0.829 respectively. Bareland, Human buildup, and grassland were found to have increased by 13.34%, 5.07%, and 29.62% respectively while sparse vegetation, dense vegetation, and water bodies were found to have decreased by 44.10%, 17.82%, and 13.34% respectively between 1996 and 2008. Likewise, there was decrease in grassland area (-26%), dense vegetation area (-9.48%), sparse vegetation area (-5%), water bodies (-0.12%), and increase in Bareland (+20%) and Human buildup (+20.6%) in between 2008 to 2020. Eight key drivers of LULC, development of infrastructure, government policy, plans, and land market, forest encroachment, forest, and its products, political condition, economic opportunities, and hotel and tourism activities, were recognized in the study area. Further research is required to determine the specific ramifications of the aforementioned LULC change drivers, as well as the area's long-term viability.